2010
DOI: 10.1186/1743-8454-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Congenital myelomeningocele - do we have to change our management?

Abstract: BackgroundEagerly awaiting the results of the Management of Myelomeningocele Study (MOMS) and with an increasing interest in setting up intrauterine myelomeningocele repair (IUMR), the optimal management of patients suffering from congenital myelomeningocele (MMC) has become a matter of debate again. We performed a cross-sectional study at our referral-center for MMC to determine the outcome for our expectantly managed patients.Materials and methodsA computed chart review at our institution revealed 70 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…For patients with myelomeningoceles, hydrocephalus is common [6][7][8][9][10][11][12][13]. Traditionally, shunting rates in the literature have ranged from 57 to 86% [14][15][16][17][18][19]. In 2018, Kim et al [20] reported that the rate of surgical treatment for hydrocephalus in the National Spina Bifida Patient Registry was 79.99%.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with myelomeningoceles, hydrocephalus is common [6][7][8][9][10][11][12][13]. Traditionally, shunting rates in the literature have ranged from 57 to 86% [14][15][16][17][18][19]. In 2018, Kim et al [20] reported that the rate of surgical treatment for hydrocephalus in the National Spina Bifida Patient Registry was 79.99%.…”
Section: Discussionmentioning
confidence: 99%
“…1 The incidence of myelomeningocele is approximately 1-2 cases every 1000 live births but differs widely from one country to the other. [2][3][4] A n a b n o r m a l i n t r a u t e r i n e position causes significant congenital orthopedic diseases that worsen during early childhood due to muscle imbalance, postural effects, growth, etc. Eighty percent of children with upper lumbar injuries have short stature; the causes include lower limb hypoplasia, scoliosis, 1 recurrent urinary tract infections, chronic renal failure, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, the literature puts the average weight of a patient undergoing ex utero MMC closure at approximately 3 kg. 7 , 8 Performing an operation on an extremely low birth weight neonate presents many risks and challenges, regardless of the type of surgery. The surgical technique is complicated by diminutive anatomical structures; meticulous hemostasis is essential; and maintenance of physiological conditions for the patient (temperature, hemodynamics) requires specialized anesthesiology care.…”
Section: Discussionmentioning
confidence: 99%